Economic Analysis of Law in Increasing Value Added Tax Rate Policy - Azhariani Fitri, Nabiela; Luth, Thohir; Hamidah, Siti (International Journal of Business, Law, and Education, 2024)
The policy of increasing the value-added tax (VAT) rate by 11% was implemented in 1st April 2022, with further increase to 12% scheduled by Januari 2025. This policy sparked both support and criticism. This study aims to analyze the concept of VAT rate increase policy aligns with the utility principle through the lens of economic analysis of law. The research adopts a juridical-normative methodology, utilizing statutory and conceptual approaches. Legal issues requires an interdisciplinary approach, which integrates law with other disciplines, especially economics, to provide a comperhensive solution. This approach eludicates economic consequenses of legal implementation and examines how law can shape economic behavior. The policy of increasing the VAT rate must lead to an increase in state revenue to enhance public welfare through efficient public serice programs and effective redistribution of tax revenue,thereby improving the quality of life for the population without causing significant harm to specific groups